2021
DOI: 10.3390/biom11050698
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulants Application: A Low Input Cropping Management Tool for Sustainable Farming of Vegetables

Abstract: Biostimulants, are a diverse class of compounds including substances or microorganism which have positive impacts on plant growth, yield and chemical composition as well as boosting effects to biotic and abiotic stress tolerance. The major plant biostimulants are hydrolysates of plant or animal protein and other compounds that contain nitrogen, humic substances, extracts of seaweeds, biopolymers, compounds of microbial origin, phosphite, and silicon, among others. The mechanisms involved in the protective effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 241 publications
(251 reference statements)
0
54
0
Order By: Relevance
“…Fungi have the ability to interact with the plant through the roots in various ways, ranging from mutualistic symbioses to parasitism [19,20]. In particular, mycorrhizal fungi are a heterogeneous group of taxa that establish symbioses with over 90% of all plant species and find numerous applications in modern horticulture [21][22][23]. Moreover, the application of biostimulants obtained from plant or seaweed extracts, as well as from the residues of crops, has shown positive results in plant growth as well as in plant adaptation to stress [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi have the ability to interact with the plant through the roots in various ways, ranging from mutualistic symbioses to parasitism [19,20]. In particular, mycorrhizal fungi are a heterogeneous group of taxa that establish symbioses with over 90% of all plant species and find numerous applications in modern horticulture [21][22][23]. Moreover, the application of biostimulants obtained from plant or seaweed extracts, as well as from the residues of crops, has shown positive results in plant growth as well as in plant adaptation to stress [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, urgent measures are needed to ensure food security, especially when considering the rapidly increasing global population and the growing demands for quality foods [6]. For this purpose, several means have been suggested during the last years including the use of cost-effective practices such as the application of biostimulants, the grafting of vegetables to tolerant rootstocks and the cropping of alternative and tolerant species, among others [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been found that the positive effects of protein hydrolysates are associated with the upregulation of metabolites involved in plant growth processes and the provocation of various activities similar to those caused by the hormones [31,32]. This enhancement of plant metabolism promotes plant respiration, photosynthesis and protein synthesis processes, thus improving crop yield and quality [30,33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that when organic matter is applied to the soil, it improves the growth and morphology of the roots, increases the absorption of nutrients and the efficiency of their use, improves crop yields and, finally, increases the quality of the fruit [32,33]. According to Garcia et al [34] and Conselvan et al [35], humic substances could promote plant growth by producing effects very similar to those of hormones.…”
Section: Discussionmentioning
confidence: 99%